Social and Economic Aspects of the Exodus of Syrian Refugees to Jordan and Lebanon - E., Nadirova G.; D., Amrayev D. (Farabi Journal of Social Sciences, 2019)
The article deals with the analysis of ethno-migration processes, which became the consequences of civil war in Syria, full of violent acts against humanity and civil rights, that has led to a mass exodus of Syrian peoples, its influence on the region of Middle East , its impact on the geopolitical policies. The Arab Spring dramatically affected all countries of the Middle East as well as their neighbors and allies, which completely shaped geopolitics of the region and caused the start of ethnic – migration processes. We try to give an insight into the formation of the migration crisis in the region and define the role and significance of the actions of international community towards the provided problems. Keywords: Syrian refugees, migration crisis, Jordan, Lebanon, economic,